Factors Related To The Presence of Aedes Aegypti Larvae and their Density in Elementary School Environments - Ratna Kurniawati; Martini Martini; Nur Wahyuningsih; Dwi Sutiningsih (Journal of Health Sciences and Surveillance System)
Background: Dengue fever in Indonesia is still high, and Bandung ranked the highest in the 33rd week of 2023. Dengue fever is a neglected tropical disease transmitted through the bite of Aedes aegypti. The school environment is at risk of DHF transmission because the biting time of Aedes aegypti coincides with student learning hours. The aim of this study was to determine the presence of Aedes aegypti larvae and their density in the elementary school environment.Methods: This study is a quantitative study with a cross-sectional design. The population of this study was all elementary schools in Bandung City, with 59 samples based on Slovin. The sample was determination using random number generation.Results: Environmental conditions of elementary schools are associated with the presence of larvae, with a P-value of 0.016. Observation results showed that 23 (39%) elementary schools found Aedes aegypti larvae. The House Index (HI) calculation was 39% and it was categorized at level 6 in the Fluke Index table. This indicates a high density of larvae. Breeding sites with larvae were in flower vases and water reservoirs in dispensers.Conclusion: Overall, our research findings indicate that the environment is a factor related to the discovery of Aedes aegypti larvae in elementary schools. With a high density of mosquito larvae, the school environment has the potential to spread dengue fever quickly.